How Do Respondents Attend to Verbal Labels in Rating Scales?. Issue 1 (February 2014) - Menold, Natalja; Kaczmirek, Lars; Lenzner, Timo; Neusar, Aleš
Two formats of labeling in rating scales are commonly used in questionnaires: verbal labels for end categories only (END form) and verbal labels for each of the categories (ALL form). We examine attention processes and respondents' burden in using verbal labels in rating scales. Attention was tracked in a laboratory setting employing eye-tracking technology. The results of the two experiments are presented: One applied seven and the other applied five categories in rating scales comparing END and ALL forms ( n = 47 in each experiment). The results show that the ALL form provides higher reliability, although the probability that respondents attend to a verbal label seems to decrease as the number of verbally labeled categories increases.